Influencia de la sobrecarga horaria, en la deserción laboral de los trabajadores de la empresa almapo s.r.l. departamento la libertad, provincia de trujillo, durante el año 2012 - Aguirre Escobedo, Elisabet Mariela (2013)
This thesis was carried out in order to explain the "Influence of the overhead time in labor attrition Company workers Almapo SRL Department La Libertad, Provincial the Trujillo, during the year 2012." Research is descriptive in nature and used deductive-inductive methods, statistics, applying the theories of observation, interview and survey. The study was conducted at the Company Almapo SRL, with the universe Sampling Area 50 warehouse workers, consisting of drivers, guards, warehouse assistants, delivery and cleaning.Also discloses the presentation of results and discussion, framed in a theoretical basis, with qualitative and quantitative data were obtained from the research, all this information give support to the assumptions made at the beginning of the thesis plan. The results obtained show that the information on workload dropout influences employee job Almapo SRL Company conclude himself from dropping out because they feel dissatisfaction with the failure to recognize their overtime and show exhaustion and tiredness in the performance of its functions. The investigation allowed us to determine the influence of recharge on hourly labor attrition employers Almapo Company SRL, causing poor job performance and dissatisfaction by not recognizing their overtime. We also managed to identify the levels of satisfaction of non-recognition of their employers overtime and description of employers who have low job performance generated by the overload time.